2022
DOI: 10.3390/ph15030293
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Effects of Gami-Yukmijihwang-Tang on the Lipopolysaccharide-Induced Hippocampus Oxidation and Inflammation via Regulation of Sirt6

Abstract: Yukmijihwang-Tang is widely used in traditional Korean medicine to treat age-related disorders. In the present study, we re-prescribed Gami-Yukmijihwang-Tang (YJT), which is slightly modified from Yukmijihwang-Tang by adding more medicinal plants to evaluate its pharmacological effects on underlying mechanisms against repeated lipopolysaccharide (LPS)-injection-induced neuroinflammation in the hippocampus regions. C57BL/6J male mice (16–24 weeks old) were divided into six groups: (1) the control group (DW with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
0
0
0
Order By: Relevance
“…Yukmijihwang-tang (YJT) contains six medicinal herbs, such as Rehmannia glutinosa, Cornus officinalis, Dioscorea batatas, Alisma orientale, Poria cocos, and Paeonia suffruticosa, in traditional Korean medicine (TKM) [45]. YJT is widely used in TKM to treat age-related disorders, such as Alzheimer's disease [46]. An in vivo study showed that YJT, at a dosage of 300 mg/kg in the treated group, significantly increased the length of the proximal tibia in the growth plate of female SD rats.…”
Section: Yukmijihwang-tang (Yjt) Herbal Formulationmentioning
confidence: 99%
“…Yukmijihwang-tang (YJT) contains six medicinal herbs, such as Rehmannia glutinosa, Cornus officinalis, Dioscorea batatas, Alisma orientale, Poria cocos, and Paeonia suffruticosa, in traditional Korean medicine (TKM) [45]. YJT is widely used in TKM to treat age-related disorders, such as Alzheimer's disease [46]. An in vivo study showed that YJT, at a dosage of 300 mg/kg in the treated group, significantly increased the length of the proximal tibia in the growth plate of female SD rats.…”
Section: Yukmijihwang-tang (Yjt) Herbal Formulationmentioning
confidence: 99%